The Ukrainian-Russian interference in the grammar of the Ukrainian dialects spread in the area between the Danube and the Dniester rivers (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the investigation of the grammatical phenomena in the Ukrainian dialects spread in the multi-lingual area between the Danube and the Dniester rivers, stimulated by the interference of the Ukrainian and Russian languages. The author characterizes factors, conditioning the results of the Russian influence in this region and the common South-Bessarabia elements in the grammar of the Ukrainian and Russian dialects.
Keywords: dialect; grammatical form; interlanguage interference; areal